Nitrogen fertilisation and nitrate pollution of groundwater in sandy soils - Yusop, Mohd. Khanif; Van Cleemput, Oswald; Baert, L. (Elsevier, 1984)
The study of the relation between N fertilisation and groundwater pollution was carried out on two fields in the sandy area of Belgium during a two-year period. The fields under study were grown with maize and barley and received fertiliser N and manure at normally applied rates. The N03- -N and Cl “content of the groundwater at 0.5, 1.0, 1.5 and 2.0 m depth was monitored every two weeks. The total rainfall during the two consecutive years was about 800 mm. On one of the fields, the N03-N content at all depths was most of the time above 11·3 mg N03-N dm3, the WHO safe limit. However, on the other field the nitrate level was much lower, except at 0·5 m depth. The difference between the two fields was attributed to differences in the rate of N input. The fluctuations during the two-year study were influenced by N fertilisation and rainfall distribution. The N03- -N/CI- ratio indicated that denitrification in the deeper zones of the soil was not prominent.